Reopening America's Schools During the COVID-19 Pandemic: Protecting Asian Students From Stigma and Discrimination - Akiba, Daisuke (Frontiers in Sociology, 2020)
The COVID-19 outbreak has prompted a rise in stigma and discrimination against people of Asian descent in many areas in the world, including the United States1. Anti-Asian hate incidents, which have ranged from verbal attacks, refusal of service to physical assault, continue to transpire in the U.S., and they put psychological and physical well-being of Asian children at increased risk. Discussions toward reopening of U.S. schools thus far, however, seem to have exclusively included the infection-related concerns and pedagogical consequences of continued disruptions in face-to-face instructions. Hence, educators, policymakers, and other stakeholders need to have plans in place to ensure that reopening of schools will be a smooth experience for students of all backgrounds.